The Effect of Love of Money and Locus of Control on Financial Management of Students in the Faculty of Economics and Business, Tanjungpura University - Lestaluhu, Muthi'ah Faradiba; Yunita, Khristina; Ikhsan, Syarbini (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
This study aims to determine the effect of love of money and locus of control on the financial management of students in the Faculty of Economics and Business, Tanjungpura University. The method used in this study is quantitative with a purposive sampling technique. The research sample consists of 50 students from the 2021 batch of the Faculty of Economics and Business, from the Accounting, Management, and Development Economics study programs, which were obtained through the distribution of questionnaires (Google Form) that have passed validity and reliability tests. The results of this study show that there is a negative influence of the love of money variable on students' financial management, meaning that the higher the effect of love of money, the lower the students' financial management. On the other hand, the locus of control variable shows a positive influence on students' financial management, meaning that the higher the locus of control, the higher the level of financial management.